2020
DOI: 10.1016/j.heliyon.2020.e04392
|View full text |Cite
|
Sign up to set email alerts
|

Alpha glucosidase inhibition activity of phenolic fraction from Simarouba glauca: An in-vitro, in-silico and kinetic study

Abstract: A phenolic rich fraction purified from Simarouba glauca leaves was effective in alpha glucosidase inhibition. The purified fraction named ‘fraction-14’ had shown significant inhibition of yeast alpha glucosidase enzyme activity (IC 50 = 2.4 ± 0.4 μg/mL) when compared to anti-diabetic drug acarbose (IC 50 = 2450 ± 24 μg/mL). The purified fraction also had reasonable DPPH (IC 50 = 14.4 ± 0.1 μg/mL) and ABTS (IC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 61 publications
1
16
0
2
Order By: Relevance
“…The acarbose, miglitol, and voglibose which are standard inhibitors were used as controls during the study. The present study revealed that some of the ‘lead hit compounds’ including the recently identified compounds by our group have better binding affinity than the available drugs ( Mugaranja and Kulal, 2020 ). Further, the drug likeliness properties of the ‘lead hit compounds’ evaluated by absorption, distribution, metabolism, excretion, and toxicity (ADMET) test provides additional evidence to consider them as effective starch hydrolysing enzyme inhibitors.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…The acarbose, miglitol, and voglibose which are standard inhibitors were used as controls during the study. The present study revealed that some of the ‘lead hit compounds’ including the recently identified compounds by our group have better binding affinity than the available drugs ( Mugaranja and Kulal, 2020 ). Further, the drug likeliness properties of the ‘lead hit compounds’ evaluated by absorption, distribution, metabolism, excretion, and toxicity (ADMET) test provides additional evidence to consider them as effective starch hydrolysing enzyme inhibitors.…”
Section: Introductionmentioning
confidence: 60%
“…In the present study total of 218 compounds have been docked against starch hydrolysing enzymes along with standard AAI and AGIs. Recently identified four compounds from Simarouba glauca ( Mugaranja and Kulal, 2020 ) are also included in this study along with the compounds identified by others ( Alves et al., 2014 ; Jiao et al., 2011 ; Kubo et al., 1993 ; Tan et al., 2012 ). The 2D structures of the majority of the compounds were retrieved from the PubChem database ( https://pubchem.ncbi.nlm.nih.gov/ ) in sdf format.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purified fractions of Simarouba glauca and isolated phytocompound, Cyanidin-3-O-(2′galloyl)-galactoside exhibited stronger α-glucosidase enzyme inhibition both in in-vitro and in-silico study. The major interacting amino acids involved were His245, Pro309, Asp408, 349, Glu304, Arg439, Phe157, − 177, − 310, − 231, − 311, − 158, − 300, and Tyr313 for Cyanidin-3-O-(2′galloyl)-galactoside and Pro309, His239, − 279, Asp349, Ser156, Arg439, Thr215, Glu276, Asp214, Phe310, − 300, − 157, − 177, − 311, − 158, Tyr17, and Tyr313 for acarbose, respectively [44]. The biological properties of any plant extracts may be attributed to the phytochemicals present in the plant.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1 mg of an α-glucosidase enzyme from S. The inhibitory activity of α-glucosidase was calculated based on the absorption values at the wavelength of 400 nm using a UV-Vis spectrophotometer 13 . The IC50 value, whereas the extract concentration can inhibit 50% of the α-glucosidase enzyme activity, was calculated based on the linear regression equation 14 .…”
Section: Antidiabetic Activity Assaymentioning
confidence: 99%